Effect of Bandpass Filter Bandwidth on the Performance of Linear Cavity Multiwavelength BEFL - Mansoor, A; Nan, PY; Azhar, H; Rashid, A; Yusoff, Z; Marinah Othman (IEEE, 2024)
Date of Conference: 28-30 October 2013 Conference Location: Melaka, Malaysia